Radar altimetry backscattering signatures at Ka, Ku, C, and S bands over West Africa. (2015) - Frappart, F.; Fatras, C.; Mougin, E.; Marieu, V.; Diepkilé, A.T.; Blarel, F.; Borderies, P.
Highlights: Comparisons of radar altimetry backscattering responses at Ka, Ku, C and S-bands. Stable responses over stone and sand deserts and non-inundated tropical forests. Variable responses over savannas along hydrological and vegetation cycles. Radar altimetry echoes can be used to detect soil moisture and flood. Abstract: This study presents a comprehensive comparison of radar altimetry signatures at Ka-, Ku-, C-, and S-bands using SARAL, ENVISAT and Jason-2 data over the major bioclimatic zones, soil and vegetation types encountered in West-Africa, with an emphasis on the new information at Ka-band provided by the recently launched SARAL–Altika mission. Spatio-temporal variations of the radar altimetry responses were related to changes in surface roughness, land cover and soil wetness. Analysis of time series of backscattering coefficients along the West African bioclimatic gradient shows that radar echoes at nadir incidence are well correlated to soil moisture in semi-arid savannah environments. Radar altimeters are able to detect the presence of water even under a dense canopy cover at all frequencies. But only measurements at Ka-band are able to penetrate underneath the canopy of non-inundated tropical evergreen forests.